Electronic Banking Service Quality and Product Features on and Satisfaction Customer Loyalty Bank BJB Bandung Area - Setiarini, Mersiana; Jusuf, Eddy; Juju, Undang (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2023)
This research is motivated by the demands of the duties and obligations of the banking world, which not only make customers interested, but also make these customers a source of profit for the bank but also make customers loyal. The results of this research provide an overview of Bank BJB in its services to its customers. The population of this research is bank bjb customers with a research sample of 400 respondents. In order to achieve the objectives of this research, questionnaire data from respondents were tested using the Structural Equation Modeling (SEM) method using LISREL 8.8 software. Based on the research results, it was found that service quality and bjb Electronic Banking product features significantly influence consumer satisfaction, service quality influences customer satisfaction, product features influence customer satisfaction, customer satisfaction influences customer loyalty.